2018
DOI: 10.1002/pbc.27376
|View full text |Cite
|
Sign up to set email alerts
|

From thrombasthenia to next generation thrombocytopenia: Neonatal alloimmune thrombocytopenia induced by maternal Glanzmann thrombasthenia

Abstract: Pregnant GT patients should be examined for platelet antibodies. Assessment and management protocols (including treatment with intravenous immunoglobulins) for fetal and neonatal alloimmune thrombocytopenia should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…13 In a previous article, Léticée et al 14 reported a case of intrauterine death due to intracranial hemorrhage in a mother with GT and positive antibodies at 31 weeks of gestation. In another study, Barg et al 15 reported that three out of nine newborns had severe thrombocytopenia, and all three babies were delivered by mothers with positive antibodies. Studies show that large doses of uterine contractions prevent PPH.…”
Section: To Editormentioning
confidence: 96%
“…13 In a previous article, Léticée et al 14 reported a case of intrauterine death due to intracranial hemorrhage in a mother with GT and positive antibodies at 31 weeks of gestation. In another study, Barg et al 15 reported that three out of nine newborns had severe thrombocytopenia, and all three babies were delivered by mothers with positive antibodies. Studies show that large doses of uterine contractions prevent PPH.…”
Section: To Editormentioning
confidence: 96%
“…11 Similarly, Barg et al, in a tertiary center, recently showed that 3 out of 9 newborns of 5 immunized GT women had severe thrombocytopenia. 20 On the other hand, a recent survey did not provide evidence that maternal anti-HLA class I antibodies are a strong risk factor for fetal and neonatal alloimmune thrombocytopenia, 23 except in rare cases. 24 However, this study was not specific to GT, and anti-integrin antibodies may have different pathological effects.…”
Section: Prepregnancy Counselingmentioning
confidence: 97%
“…Pregnancy is a recognized risk period for women with GT (Figure 1). 8,11,12,[20][21][22] Even for women who had received prophylaxis against postpartum hemorrhage (PPH), the reported prevalence of hemorrhages at delivery is high (40% to 50%), although studies do not always detail blood loss volume or manner of assessment or whether it occurred pre-, peri-, or postnatally. 11,12 Pregnancy should also be closely monitored for anti-a IIb b 3 immunization.…”
Section: Prepregnancy Counselingmentioning
confidence: 99%
“…42 As immunoreactive epitopes in FNAIT are primarily located in the extracellular regions of the platelet β3 integrin, this model mimics the FNAIT observed in newborns of mothers with Glanzmann thrombasthenia, a disorder caused by mutations in the genes coding for integrin αIIbβ3. 43 More recently, using the CRISPER technology, Zhi et al have generated an HPA-1a alloantigen-specific mouse model of FNAIT. 44 The pups of pre-immunized wild type female mice bred with HPA-1a positive male mice have been found to be severely thrombocytopenic and had bleeding symptoms.…”
Section: Antibody Parametersmentioning
confidence: 99%